Predator–prey interactions between native brine shrimp Artemia parthenogenetica and the alien boatman Trichocorixa verticalis: influence of salinity, predator sex, and size, abundance and parasitic status of prey - Céspedes,Vanessa; Sánchez,Marta I.; Green,Andy J. (PeerJ, 2017)
Trichocorixa verticalis (T. verticalis), native to North America and the Caribbean islands, is an invasive waterboatman species (Corixidae) in the southwest of the Iberian Peninsula. Previous studies in the native range have suggested that predation by T. verticalis can regulate the abundance of Anostracan and Cladoceran zooplankton in saline ecosystems, causing increases in phytoplankton through a trophic cascade. In this experimental study, we tested the predator–prey relationship between the native brine shrimp Artemia parthenogenetica, and T. verticalis from the Odiel salt ponds in SW Spain. In three experiments, we investigated (1) the effects of Artemia life stage (metanauplii, juveniles, and adults), (2) abundance (three, six, and 12 adult Artemia) and (3) parasitic status (Artemia infected with avian cestodes or uninfected) on predation rates by T. verticalis. We also considered how predation rates in all three experiments were influenced by the sex of T. verticalis and by different salinities (25 and 55 g l−1). Experiment 1 showed that predation rates were highest for metanauplii, possibly because their photophilic behavior makes them more prone to predation. In Experiment 2, we found that predation rate was higher for female T. verticalis and the higher salinity, although the strength of the sex effect varied between treatments. Experiment 3 showed that T. verticalis selectively predated adult Artemia infected with cestodes (red in color), as previously reported for predation by avian final hosts. Collectively, these results indicate that T. verticalis are important predators in their introduced range, and are likely to reduce the abundance of Artemia in more salt ponds as they expand their range, thus increasing phytoplankton abundance through trophic cascades.
Keywords: Artemia; Trichocorixa verticalis; Cestodes; Invasive species; Corixidae; Salt ponds